2021
DOI: 10.1111/ijcp.14917
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is associated with a greater number of long‐term post‐COVID symptoms and poor sleep quality: A multicentre case‐control study

Abstract: Background Obesity is a risk factor associated with higher mortality at the acute phase of COVID‐19; however, its influence on post‐COVID symptoms is not known. Objective Our aim was to investigate if obesity is a risk factor for the presence of long‐term post‐COVID symptoms in hospitalised COVID‐19 survivors. Methods A multicentre case‐control study including patients hospitalised during the first wave of the pandemic was performed. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 17 publications
1
30
2
1
Order By: Relevance
“…Overweight and obesity have been found to correlate with higher susceptibility to contracting COVID-19 leading to hospital admissions, length of hospital stay, and risk of mortality ( 26 ). Fernandez-de-Las-Penas et al found in their study that a BMI > 30 kg/m 2 could be independently linked to a larger number of post-COVID-19 symptoms, including poor sleep quality, 7 months after hospitalization due to COVID-19 ( 27 ).…”
Section: Discussionmentioning
confidence: 98%
“…Overweight and obesity have been found to correlate with higher susceptibility to contracting COVID-19 leading to hospital admissions, length of hospital stay, and risk of mortality ( 26 ). Fernandez-de-Las-Penas et al found in their study that a BMI > 30 kg/m 2 could be independently linked to a larger number of post-COVID-19 symptoms, including poor sleep quality, 7 months after hospitalization due to COVID-19 ( 27 ).…”
Section: Discussionmentioning
confidence: 98%
“…These results are consistent with previous reports in the medical literature that obesity and female sex are risk factors for long COVID. 6 , 7 , 8 However, The PHOSP-COVID Collaborative Group's findings add to the evidence base by confirming these associations in a large cohort with long-term follow-up. 2 The association between obesity and severe long COVID might be expected because the multisystemic changes (ie, hormonal, metabolic, and a pro-inflammatory state) associated with obesity 9 could promote the maintenance of a systemic inflammation.…”
mentioning
confidence: 79%
“…Some studies showed no correlation between the prolonged COVID symptoms and comorbidities of patients [ 25 , 33 ], similar with our findings. However, comorbidities such as hypertension, diabetes and dyslipidemia could be indirect risk factors to Long COVID as they are commonly associated with obesity that might increase the likelihood of Long COVID [ 25 , 34 ].…”
Section: Discussionmentioning
confidence: 99%